2020
DOI: 10.1002/ece3.6417
|View full text |Cite
|
Sign up to set email alerts
|

Honey bees and wild pollinators differ in their preference for and use of introduced floral resources

Abstract: Introduced plants may be important foraging resources for honey bees and wild pollinators, but how often and why pollinators visit introduced plants across an entire plant community is not well understood. Understanding the importance of introduced plants for pollinators could help guide management of these plants and conservation of pollinator habitat. We assessed how floral abundance and pollinator preference influence pollinator visitation rate and diversity on 30 introduced versus 24 native plants in centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…For example, honeybees ( A. mellifera ) or the sweat bee L. tegulare were more abundant on non‐native plants than on native plants, while other polylectic bees, such as X. virginica or L. trigeminum , were more abundant on native than on non‐native plants. This result supports previous findings showing bee species‐specific responses to non‐native plants (Pardee & Philpott, 2014; Schweiger et al., 2010; Urbanowicz et al., 2020), which may be due to species‐specific nutritional requirements (Leonhardt & Blüthgen, 2012; Nicolson, 2011; Vaudo et al., 2016), previous experiences (Harmon‐Threatt & Kremen, 2015; Vaudo et al., 2015), or competition (Somme et al., 2015; Wilms et al., 1996).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For example, honeybees ( A. mellifera ) or the sweat bee L. tegulare were more abundant on non‐native plants than on native plants, while other polylectic bees, such as X. virginica or L. trigeminum , were more abundant on native than on non‐native plants. This result supports previous findings showing bee species‐specific responses to non‐native plants (Pardee & Philpott, 2014; Schweiger et al., 2010; Urbanowicz et al., 2020), which may be due to species‐specific nutritional requirements (Leonhardt & Blüthgen, 2012; Nicolson, 2011; Vaudo et al., 2016), previous experiences (Harmon‐Threatt & Kremen, 2015; Vaudo et al., 2015), or competition (Somme et al., 2015; Wilms et al., 1996).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, studies found bee species richness either higher (Bartomeus et al, 2008;Lopezaraiza-Mikel et al, 2007;Vilà et al, 2009), lower Morandin & Kremen, 2013), or the same (Pardee & Philpott, 2014) on non-native plants versus native plants. The majority of this research has been conducted in Europe and the United States, while studies from the southern hemisphere are still scarce (but see Morales and Aizen (2006) and Gibson et al (2013) for examples from Argentina and South Africa) despite the often negative effects of non-native (invasive) plant species on native flora and fauna (Bellard et al, 2017;Van Kleunen et al, 2015). Most of these studies focused on invasive non-native plants instead of directed pollinator friendly plantings and were observational, rather than the result of hypothesis-driven field trials.…”
mentioning
confidence: 99%
“…Per species, we estimated the number of floral units per stem and averaged this across the sites and weeks the species was in bloom (minimum five measurements per species). We define a floral unit as being the typical unit (single flower or inflorescence) that a bee typically foraged from 53 . This definition of a floral unit was also consistent with the amount of plant material we used for each sample during parasite screening.…”
Section: Methodsmentioning
confidence: 99%
“…In environments with very few bee-friendly native plants, some exotic invasive species can help populations to recover. Again, these choices should be taken based on strong empirical evidence since a recent study in New-York suggested that many exotic plants could mainly help honeybees more than wild bees [220]. In these anthropogenic environments, the way to manage bee-friendly areas have also to be re-think, notably by finding alternatives to pesticides.…”
Section: Discussionmentioning
confidence: 99%